2014
DOI: 10.1097/prs.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation and Progressive Calcification as a Result of Fat Necrosis

Abstract: Therapeutic, V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 21 publications
2
86
0
3
Order By: Relevance
“…4B, black) surrounded by inflammatory infiltrate (Fig. 4B, red nuclei) (Hanami, Hiraiwa and Yamamoto, 2012;Mineda et al, 2014;Misumi et al, 2019). H&E staining also showed that IL-1R -/-vWAT had large, acellular regions surrounded by inflammatory infiltrate (Fig 4C).…”
Section: Il-1 R Signaling Protects Adipose and Liver From Acute Pathomentioning
confidence: 87%
“…4B, black) surrounded by inflammatory infiltrate (Fig. 4B, red nuclei) (Hanami, Hiraiwa and Yamamoto, 2012;Mineda et al, 2014;Misumi et al, 2019). H&E staining also showed that IL-1R -/-vWAT had large, acellular regions surrounded by inflammatory infiltrate (Fig 4C).…”
Section: Il-1 R Signaling Protects Adipose and Liver From Acute Pathomentioning
confidence: 87%
“…Neuber was the first author to describe the use of autologous fat as a filling material in 1893, and since the first attempts, the results of free fat autotransplantation have been disappointing [20]. Implanted fat resorbs at an unpredictable rate that ranges from 20% to 90%, requiring overcorrection and additional grafting [21]. Various studies have been performed to increase the survival of free fat grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Es besteht jedoch ein höheres Risiko fĂŒr Nekrosen, chronische EntzĂŒndungen und die Entwicklung von sog. Ölzysten [67,68], insbesondere bei zu oberflĂ€chlichen Injektionen. Hinzu kommt ein gesteigertes Risiko fĂŒr Nebenwirkungen, die mit der Gewinnung der Fettzellen einhergehen, wie z.…”
Section: Autologer Fetttransferunclassified